The effects of a two-week neuromuscular intervention on biopsychosocial variables in people with patellofemoral pain: an observational study - Lack, Simon David; Bartholomew, Clare; North, Thomas; Miller, Stuart Charles; Neal, Bradley Stephen (Frontiers in Sports and Active Living, 2023)
Introduction: Patellofemoral pain (PFP) is common and predominately affects active populations. Altered biomechanics and psychosocial variables have been reported in people with PFP, but the effects of neuromuscular exercise on these variables is unknown. We aimed to investigate changes in biopsychosocial measures following a two-week neuromuscular intervention in people with PFP. Materials and Methods: We measured pain (visual analogue scale), function (Kujala), activity level (Tegner), psychological well-being (Orebro) and lower-limb isometric strength (handheld dynamometry), three-dimensional (3D) lower limb kinematics, and surface electromyography (sEMG), in people with PFP. 3D lower-limb kinematics and sEMG were synchronously sampled during step-up, step-down, and overground running. All measures were repeated after participants had completed a two-week neuromuscular intervention consisting of three exercises completed once per day, five days per week. Results: 18 participants completed pre/post testing (60% females, mean age 30.6 years ±7.0, height 173.4cm ±10.4, mass 70.2kg ±12.4, symptom duration 39.0 months ±58.8), with three of 21 participants lost to follow-up. Across all clinical measures, muscle onsets, muscle activation and kinematics, the 95% bootstrapped CI of the mean difference contained the null hypothesis following the two-week neuromuscular intervention. Conclusion: A two-week neuromuscular intervention did not change biomechanical or psychosocial measures in people with PFP. Interventions with a longer duration or greater load magnitude are required to fully evaluate the biopsychosocial mechanisms of effect for exercise in people with PFP.